Economic and geographical and socio-economic differences of regions of the Republic of Belarus as a basis for improvement of administrative-territorial division - Antipova, Ekaterina A.; Shavel, Aleksej N.; Zaprudskij, Ilja I. (Journal of the Belarusian State University. Geography and Geology, 2019)
The article is devoted to the analysis of economic-geographical and socio-economic differences of the regions of the Republic of Belarus in order to improve the administrative and territorial division (ATD). The decisive role of the Belarusian scientific school of economic geography in developing of the principles of the ATD of Belarus at various periods of development is shown. The historical stages of formation, advantages and disadvantages of the current system of the ATD of the Republic of Belarus are revealed. The positive and negative international experience of conducting of administrative and territorial transformations is systematized. The significant disproportions in the resource, demographic and economic potential of the regions of Belarus and their various contributions to the social and economic development of the state are determined. Based on the centro-peripheral principle, a scheme of the regions of Belarus by the level of socio-economic development has been developed, which indicates significant changes in the development of regional economic complexes that have occurred over the past decades. About 20 % administrative districts are characterized by the properties of the center or semi-center, which have the ability to perform the functions of regional centers in the new ATD. More than 30 % administrative areas are peripheral in terms of socio-economic development. The obtained results are the basis to the need to improve the ATD of the Republic of Belarus.
Keywords: Belarusian school of economic geography; the Republic of Belarus; administrative and territorial division; regional disproportions; demographic and socio-economic differences